Risk Factors and Short-term Prognosis of Severe Neonatal Asphyxia Complicated with Acute Kidney Injury - PEI Xuejing, SHEN Huaiyun, XU Qianqian, LIU Binbin, WANG Huihui (Zhongguo quanke yixue, 2024)
Background Early diagnosis of acute kidney injury (AKI) in neonates is difficult with a high mortality rate. However, there is currently a lack of research on severe neonatal asphyxia complicated with AKI. Objective To investigate the risk factors and short-term prognosis of neonatal asphyxia complicated with AKI, and analyze the predictive value of related factors, so as to take measures to reduce the occurrence of AKI and improve the success rate of resuscitation of the neonates. Methods A total of 172 neonates with severe asphyxia who were hospitalized in the Neonatal Intensive Care Unit of the First Affiliated Hospital of Bengbu Medical College from January 2016 to January 2023 were included as the study subjects and divided into AKI group (n=43) and non-AKI group (n=129) according to whether the neonates were complicated with AKI. Clinical data and laboratory results were collected, and the short-term prognosis (survival or death during hospitalization) of the children with AKI was recorded. Multivariate Logistic regression analysis was used to explore the influencing factors of severe neonatal asphyxia complicated with AKI, and receiver operating characteristics (ROC) curve was used to explore the predictive value of related indicators for severe neonatal asphyxia complicated with AKI. Results Gestational age, birth weight, 5-min Apgar score and platelet count in AKI group were lower than those in non-AKI group, and the proportions of coma, invasive mechanical ventilation and combined respiratory failure, cystatin C (Cys C) were higher than those in non-AKI group, with statistically significant difference (P<0.05). Multivariate Logistic regression analysis showed that 5-min Apgar score (OR=1.553, 95%CI=1.193-2.021, P=0.001), invasive mechanical ventilation (OR=2.965, 95%CI=1.021-8.611, P=0.046) and blood Cys C value (OR=0.231, 95%CI=0.109-0.487, P<0.001) were the influential factors for severe neonatal asphyxia complicated with AKI. ROC curve analysis showed that the AUC of blood Cys C for predicting AKI was 0.777 (95%CI=0.701-0.854, P<0.05), and the AUC of 5-min Apgar score for predicting AKI was 0.792 (95%CI=0.715-0.869, P<0.05). The hospitalized mortality was 51.2% (22/43) in AKI group and 21.7% (28/129) in non-AKI group, and the mortality in AKI group was higher than that in non-AKI group, the difference was statistically significant (χ2=13.572, P<0.001) . Conclusion Low 5-min Apgar score, invasive mechanical ventilation, and high postnatal blood Cys C can increase the risk of AKI in neonates with severe asphyxia. Postnatal blood Cys C and 5-min Apgar Score are reliable predictor of neonatal asphyxia complicated with AKI.